Early Identification of the Patient with Endotheliopathy of Trauma by Arrival Serum Albumin. Issue 1 (July 2018) - Gonzalez Rodriguez, Erika; Cardenas, Jessica C.; Lopez, Ernesto; Cotton, Bryan A.; Tomasek, Jeffrey S.; Ostrowski, Sisse R.; Baer, Lisa A.; Stensballe, Jakob; Holcomb, John B.; Johansson, Pär I.; Wade, Charles E.
ABSTRACT: Objective: Traumatic endotheliopathy (EoT) is associated with glycocalyx breakdown and capillary leak resulting in the extravasation of proteins. We hypothesized that lower serum albumin levels are associated with EoT, poor outcomes, and can be used for early EoT screening in trauma patients. Methods: We enrolled severely injured trauma patients with serum albumin levels available on admission. Syndecan-1 and soluble thrombomodulin were quantified from plasma by ELISA. Demographic and clinical data were obtained. We evaluated the association of serum albumin and EoT+ (syndecan-1 level ≥40 ng/mL), followed by dichotomization by serum albumin level, and subgroup comparisons. Results: Of the 258 patients enrolled 92 (36.0%) were EoT+ (syndecan-1 ≥ 40 ng/mL). Median albumin levels in the EoT+ group were 3.4 g/dL, and 3.8 g/dL in EoT− patients, P  < 0.05. In a multifactorial analysis, lower albumin levels were inversely associated with the likelihood of EoT+. With receiver characteristic curve analysis, we determined a cutoff albumin level < 3.6 g/dL for EoT+ prediction (area under the curve 0.70; 95% CI: 0.63, 0.77). After dichotomizing by albumin <3.6 or ≥3.6 g/dL, 51.5% of patients had low albumin. Low albumin patients were more likely to have EoT+, as well as higher soluble thrombomodulin (both P  < 0.05). Furthermore, they required more frequently blood transfusions, had fewer hospital-free days and higher mortality rate than those with normal albumin. Conclusions: EoT is a syndrome associated with leakage of albumin from the intravascular compartment, which re-emphasizes that arrival albumin may be a novel and timely approach to the identification of patients needing endothelial rescue therapy.